Association of neutrophil/high-density lipoprotein cholesterol ratio with the cardiovascular-kidney-metabolic syndrome and its cardiovascular mortality - Xu, Yaying (Frontiers in Nutrition, 2025)
BackgroundCardiovascular-kidney-metabolic (CKM) syndrome is a novel multi-system disease defined by the American Heart Association (AHA). This study aims to investigate the associations between the neutrophil/high-density lipoprotein cholesterol ratio (NHR) and CKM syndrome and its association with cardiovascular disease (CVD) mortality.MethodsThe data for this study were derived from the National Health and Nutrition Examination Survey (NHANES) conducted from 2005 to 2018 and the National Death Index (NDI) database. Weighted multivariate logistic regression and Cox regression were the primary analytical methods. restricted cubic spline (RCS) and subgroup analyses were also carried out.ResultsA total of 13,165 participants were included in this study. The weighted mean of NHR was 3.14 ± 0.03. The prevalence rate of CKM syndrome was 17.36%. The results of the weighted logistic regression indicated that there was a positive association between NHR and CKM syndrome (ORper SD: 1.25, 95% CI: 1.10–1.42, p < 0.001). Among the quartile groups of NHR, the prevalence rate of CKM syndrome showed an increase (p for trend <0.0001). Among individuals with CKM syndrome, the results of the weighted Cox regression demonstrated that NHR also significantly predicted CVD mortality (HRper SD: 1.31, 95% CI: 1.14–1.50, p < 0.001). Among the quartile groups of NHR, the risk of CVD mortality also increased in a trend (p for trend = 0.01). Furthermore, RCS analysis showed a positive linear association between NHR and CKM syndrome (non-linear p = 0.075) and between NHR and CVD mortality (non-linear p = 0.300). The subgroup analysis suggested that the relationship between NHR and the outcomes was robust, and there was no significant interaction.ConclusionOur study demonstrates that NHR is not only associated with an increased prevalence of CKM syndrome but also serves as an effective predictor for CVD mortality in patients with CKM syndrome. This provides new insights into the clinical identification and prognostic evaluation of CKM syndrome.